Photoperiod influences the shape and scaling of freshwater phytoplankton responses to light and temperature. Issue 6 (5th April 2022) - Theus, Meredith E.; Layden, Tamara J.; McWilliams, Nancy; Crafton‐Tempel, Stephen; Kremer, Colin T.; Fey, Samuel B.
Abstract : Light fluctuations are ubiquitous, exist across multiple spatial and temporal scales, and directly affect the physiology and ecology of photoautotrophs. However, the indirect effects of light fluctuations on the sensitivity of organisms to other key environmental factors are unclear. Here, we evaluate how photoperiod regime (period of time each day where organisms receive light), a dynamic element of aquatic ecosystems, can influence the interactive effects of temperature and irradiance (intensity of light) on the growth rate of phytoplankton populations. We first completed a literature review and meta‐analysis that suggests photoperiod alters the individual effects of temperature – but not irradiance – on algal growth rates and that highlights how few studies experimentally manipulate photoperiod, temperature and irradiance. To address this empirical gap, we conducted a set of laboratory experiments on three freshwater phytoplankton species ( Chlamydomonas reinhardtii, Chlorella vulgaris and Cryptomonas ovata ). We measured performance surfaces relating growth rate to irradiance and temperature gradients for each species in constant (24:0 h of light:dark) environments. We then evaluated whether analogous surfaces measured under different photoperiods (6:18, 12:12 and 16:8 h of light:dark) and scaled by the duration of light availability could be inferred from results under constant light. For a majority of the combinations of species and photoperiods examined, photoperiod meaningfully altered the intercept and shape of performance surfaces. These differences were most pronounced under the shortest photoperiod (6:18 h light:dark), where populations underperformed expectations. Alterations to performance surfaces were non‐linear and mostly structured by temperature with higher temperatures yielding higher than anticipated growth rates. Collectively, these experiments and synthesis reveal the potential for photoperiod regime to influence the effects of temperature, irradiance and their interaction on phytoplankton growth. Beyond the environmental variables and organisms presently considered, this research highlights the capacity for dynamic, abiotic variables to exert direct effects while also influencing relationships among other environmental factors.